Synthesis, Characterization, and Applications of Copper Nanoparticles: Synthesis, Characterization, and pH-dependent Size Variation of Crystalline Copper Nanoparticles for Diverse Applications (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Copper nano particles (CuNPs) are having significant enthusiasm for the present huge research because of their perfect intriguing range of physical and chemical properties alongside their critical potential action in a wide scope of uses. In the current examination, CuNPs were orchestrated through straightforward chemical decrease strategy and considered the impact of pH uniqueness on molecule size variety. The X-beam diffraction investigation affirmed the arrangement of cubic organized CuNPs with high crystalline nature.